Developing Hypothetical Learning Trajectory of Probability Through Ethnomathematics Using the Congklak Game: Exploring Local Wisdom - Prayogo, Mochammad Reval Ardhi Yudi; Kurniasari, Santi; Martin, Azzahra Cahyaning; Sholihah, Umi Mar’atus; Sari, Yurizka Melia (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2025)
This study aims to develop a Hypothetical Learning Trajectory (HLT) in learning probability through an ethnomathematics approach using the traditional game congklak. Local culture-based learning is believed to improve the understanding of the concept of chance in a more contextual and meaningful way. The research method used was descriptive qualitative with an ethnographic approach. The results showed that learning probability by using congklak as a context can increase student engagement, help them understand the concepts of sample space, sample points, and theoretical and empirical probability more systematically. This finding confirms that the integration of ethnomathematics in learning probability not only improves students' mathematical understanding, but also contributes to the preservation of local culture. Therefore, this approach is recommended to be applied in mathematics learning, especially on chance materials.